Flapping of heavy inverted flags: a fluid-elastic instability. (10th December 2020) - Tavallaeinejad, Mohammad; Païdoussis, Michael P.; Flores Salinas, Manuel; Legrand, Mathias; Kheiri, Mojtaba; Botez, Ruxandra M.
Abstract: Abstract : Wind tunnel experiments are described in this paper, aiming to examine the global dynamics of heavy inverted flags, with a specific focus on the underlying mechanism of large-amplitude flapping, which occurs at sufficiently high flow velocities. This problem is of interest because no consensus exists as to the mechanism, specifically whether it is a vortex-induced vibration or a self-excited vibration – the answer being not only of fundamental interest, but also important for energy harvesting applications. The effect of vortex shedding from both leading and trailing edges was investigated via experiments with flags modified by serrations to the leading edge and a long rigid splitter plate at the trailing edge, so as to disrupt leading- and trailing-edge vortices and to inhibit interactions between counter-rotating leading-edge vortices, if they exist. The relatively small quantitative changes in the critical flow velocity, amplitude and frequency of oscillations, as well as the near-identical qualitative behaviour, of plain and modified flags suggests that the global qualitative dynamics of heavy inverted flags is independent of vortex shedding from the leading and trailing edges, i.e. periodic vortex shedding is not the cause but an effect of large-amplitude flapping. Additional experiments showed that the dominant frequencies of flapping and the lift force on the flag are generally not synchronized, and multiple frequencies occur in the lift signal, reinforcing the conclusion that vortex shedding is not the cause of flapping. Our experimental results suggest that self-excited vibration through a fluid-elastic instability, i.e. flutter, is the underlying mechanism for the flapping of heavy inverted flags.